Agreement of rebound and applanation tonometry intraocular pressure measurements during atmospheric pressure change - Vercellin, Alice Verticchio; Harris, Alon; Siesky, Brent; Zukerman, Ryan; Tanga, Lucia; Carnevale, Carmela; Scarinci, Fabio; Oddone, Francesco (PloS one, 2021)
This study investigated the agreement of intraocular pressure measurements using rebound tonometry and applanation tonometry in response to atmospheric changes in a hyperbaric chamber. Twelve eyes of 12 healthy subjects were included in this prospective, comparative, single-masked study. Intraocular pressure measurements were performed by rebound tonometry followed by applanation tonometry in a multiplace hyperbaric chamber at 1 Bar, followed by 2, 3 and 4 Bar during compression and again at 3 and 2 Bar during decompression. Mean differences between rebound and applanation intraocular pressure measurements were 1.6, 1.7, and 2.1 mmHg at 2, 3, and 4 Bar respectively during compression and 2.6 and 2.2 mmHg at 3 and 2 Bar during decompression. Lower limits of agreement ranged from -3.7 to -5.9 mmHg and upper limits ranged from -0.3 to 1.9 mmHg. Multivariate analysis showed that the differences between rebound and applanation intraocular pressure measurements were independent of atmospheric pressure changes (p = 0.79). Intraocular pressure measured by rebound tonometry shows a systematic difference compared to intraocular measured by applanation tonometry, but this difference is not influenced by changes of atmospheric pressure up to 4 Bar in a hyperbaric chamber. Agreement in magnitude of change between devices suggests rebound tonometry is viable for assessing intraocular pressure during atmospheric changes. Future studies should be designed in consideration of expected differences in IOP values provided by the two devices.